Development of the Social Media Engagement Scale for Adolescents - Ni, Xiaoli; Shao, Xiaoyi; Geng, Yangwen; Qu, Ran; Niu, Gengfeng; Wang, Yuping (Frontiers in Psychology, 2020)
This study aimed to develop the Social Media Engagement Scale for Adolescents (SMES-A), and evaluate its reliability and validity. The initial items were collected by open-ended questions, literature review, and suggestions from psychological experts. A total valid sample of 2519 adolescents participated in this study. The results of exploratory factor analysis (EFA) indicated that this scale was composed of three factors named affective engagement, behavioral engagement, and cognitive engagement, accounting for 56.01% of the total variance. The confirmatory factor analysis (CFA) confirmed the three-factor model. The affective engagement, behavioral engagement, and cognitive engagement were positively correlated with the criterion variables of objective social media use. The mean intra-correlation coefficient of the three factors were .523, .451 and .512. The Cronbach’s alpha coefficient of the affective engagement, behavioral engagement, and cognitive engagement were from .709 to .804. The McDonald’s omega of them were .805, .805, and .712, which showed high reliability of this three-factor structure. The test-retest reliability of the three factors were all above .68 eight weeks later. Overall, our findings suggested that SMES-A is a reliable and valid measurement to evaluate social media engagement among Chinese adolescents.